Differentiation and regeneration potential of mesenchymal progenitor cells derived from traumatized muscle tissue - Jackson, Wesley M (Blackwell Publishing Ltd, 2011)
Mesenchymal stem cell (MSC) therapy is a promising approach to promote tissue regeneration by either differentiating the MSCs into the desired cell type or by using their trophic functions to promote endogenous tissue repair. These strategies of regenerative medicine are limited by the availability of MSCs at the point of clinical care. Our laboratory has recently identified multipotent mesenchymal progenitor cells (MPCs) in traumatically injured muscle tissue, and the objective of this study was to compare these cells to a typical population of bone marrow derived MSCs. Our hypothesis was that the MPCs exhibit multilineage differentiation and expression of trophic properties that make functionally them equivalent to bone marrow derived MSCs for tissue regeneration therapies. Quantitative evaluation of their proliferation, metabolic activity, expression of characteristic cell-surface markers and baseline gene expression profile demonstrate substantial similarity between the two cell types. The MPCs were capable of differentiation into osteoblasts, adipocytes and chondrocytes, but they appeared to demonstrate limited lineage commitment compared to the bone marrow derived MSCs. The MPCs also exhibited trophic (i.e. immunoregulatory and pro-angiogenic) properties that were comparable to those of MSCs. These results suggest that the traumatized muscle derived MPCs may not be a direct substitute for bone marrow derived MSCs. However, because of their availability and abundance, particularly following orthopaedic injuries when traumatized muscle is available to harvest autologous cells, MPCs are a promising cell source for regenerative medicine therapies designed to take advantage of their trophic properties.